2017
DOI: 10.1002/jhet.3050
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Assisted Synthesis and Antimicrobial Potential of Quinoline‐Based 4‐Hydrazide‐Hydrazone Derivatives

Abstract: Quinoline is a benzo‐fused pyridine which is a therapeutically important heterocycle in medicinal chemistry research and new drug development. A series of 12 new hydrazide‐hydrazone motifs bearing quinoline core 4a–l was successfully synthesized by microwave irradiation technique. The synthesis involved four steps strategies which was initiated by ring‐opening synthetic modification of isatin to quinoline‐4‐carboxylic acid through Pfitzinger approach. The structure of the reactive intermediates 1, 2, and 3 as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…Having in view the biological potential of quinoline and sulfonamide scaffolds (especially antimicrobial) [9][10][11][12][13][14][15], as well as those one of quinoline-sulfonamide combined scaffold (especially anti-HIV-1) [16], we decide to combine the pharmacophoric properties of these core scaffolds with the complementary biological properties of counter cation M 2+ (M 2+ : Zn 2+ , Cu 2+ , Co 2+ and Cd 2+ ), with the final goal of obtaining better biological activity and better pharmacokinetic properties for our compounds. In this respect, we design two new classes of hybrid quinoline-sulfonamide complexes, namely N-(quinolin-8-yl)-4-R-benzene sulfonamide metal (II) (QBSC) and N-(quinolin-8-yl)-quinoline -8-sulfonamide metal (II) (QQSC), Scheme 1.…”
Section: Design and Chemistrymentioning
confidence: 99%
“…Having in view the biological potential of quinoline and sulfonamide scaffolds (especially antimicrobial) [9][10][11][12][13][14][15], as well as those one of quinoline-sulfonamide combined scaffold (especially anti-HIV-1) [16], we decide to combine the pharmacophoric properties of these core scaffolds with the complementary biological properties of counter cation M 2+ (M 2+ : Zn 2+ , Cu 2+ , Co 2+ and Cd 2+ ), with the final goal of obtaining better biological activity and better pharmacokinetic properties for our compounds. In this respect, we design two new classes of hybrid quinoline-sulfonamide complexes, namely N-(quinolin-8-yl)-4-R-benzene sulfonamide metal (II) (QBSC) and N-(quinolin-8-yl)-quinoline -8-sulfonamide metal (II) (QQSC), Scheme 1.…”
Section: Design and Chemistrymentioning
confidence: 99%
“…Olayinka O. Ajani et al reported synthesis and biological activities of some substituted coumarins All the compounds (1,2,3,4) showed good activity against Staphylococcus aureus and Escherichia coli and, Bacillus subtilis. 33 Al-Amiery et al have synthesized 4-[(5-mercapto-4-phenyl-4H-1,2,4triazol-3-yl)-methoxy]-2H-chromen-2-one as coumarin derivatives and their antifungal activity was determined based on the growth inhibition rates of the mycelia of strains of Aspergillus niger and Candida albicans in Potato Dextrose Broth medium (PDB) against concentrations ranging from 10 to 100µgml -1 . Two compounds (5,6) showed good activity as antifungals against fluconazole standard drug.…”
Section: Antimicrobal Activitymentioning
confidence: 99%
“…Ajani et al [55] synthesized a new class of quinolines (62a-l) bearing hydrazide-hydrazone moiety, while using MW assisted reactions, in continuation of their work in the field of antimicrobial derivatives. The reactions under MW allowed for them to obtain very good yields, high purity of compounds, and a very short reaction time (1-3 min).…”
Section: Six Membered Ring Azaheterocyclesmentioning
confidence: 99%